The Dialectic of Form and Sense in Translation between Translation Didactics and Translation Theory - BOUKAOUD, Imene (Journal of Human Sciences, 2020)
The present paper proposes a theory-based approach to translation didactics, taking the example of a very common dichotomy that is problematic for students as well as teachers in translation classes; this dichotomy contrasts literal translation to free translation. The idea is to investigate it in translation theory and find a possible, convincing and practical answer to this issue. This dichotomy (literal translation versus free translation) and other issues of great concern can find possible answers and useful solutions in the translation studies proposed by Holmes, which can represent a scientific framework for translation didactics.